Usia Ibu Sebagai Faktor Risiko Terjadinya Plasenta Previa - Salma Khairunnisa Hero; Rodiani; Giska Tri Putri (Medula, 2023)
Placenta previa is complete or partial closure of the inner cervical ostium by the placenta. Placenta previa is one of the causes of postpartum hemorrhage and is a condition that can cause morbidity and mortality for both mother and baby. Placenta previa has the potential to become an emergency. Placenta previa is located in the lower uterine segment and causes obstruction of the cervix. This can make the vaginal birth process more difficult and risky, even leading to death from bleeding. There are several factors that can be risk factors for placenta previa, namely parity, history of curettage, cesarean section, previous history of placenta previa, multiple pregnancies, tumors, and age. At the age of <20 years the reproductive system is still immature. The endometrium in the immature uterine fundus causes the placenta to attach and grow in the lower uterine segment. At the age of> 35 years, the reproductive system has decreased, one of which is a decrease in blood flow to the uterus. So that the placenta will implant in the part that has more blood flow.